2016
DOI: 10.1111/beer.12116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CSR evaluations on affective attachment to CSR in different identity orientation firms

Abstract: The goal of the present research is to examine the way in which organisational identity orientation and corporate social responsibility (CSR) interact to produce affective attachment and related beneficial behaviours among organisational members. Using a questionnaire, administered in Poland, we show that when CSR activity is viewed as authentic by employees, it leads to affective attachment to the organisation's CSR stance, while an instrumental evaluation is correlated with a negative attachment to the CSR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Thus, a code affects a company's ethical culture, which in turn fosters ethical behavior beyond the specific rules stated in the code. Evidence has shown that a company's code of ethics positively affects various elements of corporate culture, such as perceived ethical values (Valentine & Barnett, 2002), organizational commitment (Collier & Esteban, 2007;Fryzel & Seppala, 2016;Valentine & Barnett, 2003), and job satisfaction (Valentine & Fleischman, 2008), all of which contribute to ethical decision making (Craft, 2013;Lehnert, Park, & Singh, 2015). Thus, apart from a code's direct intent to forbid or demand specific actions, it contributes to a positive ethical culture, which is defined as the interplay between formal (e.g., codes) and informal elements (e.g., peer behavior).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a code affects a company's ethical culture, which in turn fosters ethical behavior beyond the specific rules stated in the code. Evidence has shown that a company's code of ethics positively affects various elements of corporate culture, such as perceived ethical values (Valentine & Barnett, 2002), organizational commitment (Collier & Esteban, 2007;Fryzel & Seppala, 2016;Valentine & Barnett, 2003), and job satisfaction (Valentine & Fleischman, 2008), all of which contribute to ethical decision making (Craft, 2013;Lehnert, Park, & Singh, 2015). Thus, apart from a code's direct intent to forbid or demand specific actions, it contributes to a positive ethical culture, which is defined as the interplay between formal (e.g., codes) and informal elements (e.g., peer behavior).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, while existing studies pay greater attention to other stakeholder groups (see discussion in Morgeson et al, ; Mueller et al, ; Peterson, ; Turker, ), research interest in employees’ perceptions of CSR activities is growing (Brammer, Millington, & Rayton, ; Collier & Esteban, ; Dawkins, Jamali, Karam, Lin, & Zhao, ; Lis, ; Maclagan, ; Peterson, ; Riordan, Gatewood, & Bill, ; Rupp et al, ; Story & Neves, ). Studies have shown that employee reactions to CSR are complex and depend on the type of CSR activities implemented, on employee values and perceptions (De Roeck & Delobbe, ; Fryzel & Seppala, ; McShane & Cunningham, ; Turker, ; Vitell & Paolillo, ), and on corporate contextual factors (Collier & Esteban, ). Existing literature, however, has rarely brought together all of these factors in a single analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The key insight of Phase 1 is that strategy‐CSR fit does have an impact on employees’ AOC, which has not yet been empirically examined in extant literature (e.g., Brammer et al, ; De Roeck & Maon, ; Fryzel & Seppala, ). This constitutes a first step to confirm the value of strategic CSR in micro‐CSR research, as it has significant positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps the main reason why literature has distinguished OI from AOC (e.g., Kim et al, ; Mueller et al, ), despite their similarity. In fact, according to social identity theory, OI is seen as an antecedent to AOC because membership to a respected company can enhance employees’ self‐concept, and through this identification process affect affective organizational commitment (De Roeck & Maon, ; Farooq et al, ; Fryzel & Seppala, ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%